The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1104/pp.51.5.907
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Naphthaleneacetic Acid Conjugation

Abstract: Formation of naphthaleneacetic acid-glucose (NAGlu) in detached leaves, floating on a-naphthaleneacetic acid-1-V4C (NAA, 0.05 microcurie per milliliter, 3.1 ,uM)-buffer solution (phosphate-citrate, pH 4.2) began immediately while there was a 2-to 4-hour lag before NAA-asparatate (NAAsp) could be detected. Subsequent increase in the NAAsp conjugate reflected a decrease in free NAA to 1 to 2 % of the total radioactivity taken up. Pretreatment with 31 gM 'C-NAA for 18 hours doubled NAAsp formation after transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
25
1

Year Published

1974
1974
1993
1993

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 31 publications
4
25
1
Order By: Relevance
“…Rhizobitoxine (1.87 ,uM) inhibited indole-3-acetic acid-induced ethylene production but did not prevent the formation of indole-3-acetylaspartic acid. In view of the similarity of these results and those previouslv obtained with a-naphthaleneacetic acid, it is concluded that ethylene has no role in the auxin-induced indole-3-acetylaspartic acid formation in cowpea leaves.Although conjugation of exogenous IAA and NAA3 with aspartic acid in plant tissues is well documented (2,5,8,(10)(11)(12), see also literature review 5), the mechanism of induction of the still unisolated (L)-aspartic acid-N-acylase, considered responsible for this conjugation (11), remains unclear. The formation of aspartic acid conjugates with both IAA and NAA usually occurs after a lag period of about 2 hr (2,5,8,11).…”
mentioning
confidence: 99%
“…Rhizobitoxine (1.87 ,uM) inhibited indole-3-acetic acid-induced ethylene production but did not prevent the formation of indole-3-acetylaspartic acid. In view of the similarity of these results and those previouslv obtained with a-naphthaleneacetic acid, it is concluded that ethylene has no role in the auxin-induced indole-3-acetylaspartic acid formation in cowpea leaves.Although conjugation of exogenous IAA and NAA3 with aspartic acid in plant tissues is well documented (2,5,8,(10)(11)(12), see also literature review 5), the mechanism of induction of the still unisolated (L)-aspartic acid-N-acylase, considered responsible for this conjugation (11), remains unclear. The formation of aspartic acid conjugates with both IAA and NAA usually occurs after a lag period of about 2 hr (2,5,8,11).…”
mentioning
confidence: 99%
“…The ability of plant tissues to conjugate IAA and NAA to glucose and aspartic acid is well established (3,9,10). We have found (11) an in situ increase in the level of auxin in AZs sections of isolated Citrus leaf during the first hours of abscission, and a marked decrease in endogenous auxin at later stages.…”
mentioning
confidence: 56%
“…Our results, however, do not exclude the possibility that auxin conjugation in the leaf blade may have a role in the regulation of abscission. We were unable to show any inductive effect of ethylene on either NAA or IAA conjugation rate (9,10). Beyer and Morgan (5) reported that ethylene-induced inhibition ofauxin transport is not due to its increased conjugation rate to aspartic acid.…”
mentioning
confidence: 73%
See 2 more Smart Citations